Intratumoral delivery of immunotherapy to treat breast cancer: current development in clinical and preclinical studies - Mantooth, Siena M.; Abdou, Yara; Saez-Ibañez, Ana Rosa; Upadhaya, Samik; Zaharoff, David A. (Frontiers in Immunology, 2024)
Breast cancer poses one of the largest threats to women's health. Treatment continues to improve for all the subtypes of breast cancer, but some subtypes, such as triple negative breast cancer, still pose present a significant treatment challenge. Additionally, metastasis and local recurrence pose are two prevalent problems in breast cancer treatment. A newer type of therapy, immunotherapy, may offer alternatives to traditional treatments for difficult-to-treat subtypes and traditional treatments. Immunotherapy engages the host's immune system to eradicate disease, with the potential to induce long-lasting, durable responses. However, systemic immunotherapy is only approved in a limited number of indications, and it benefits only a minority of patients. Furthermore, immune related toxicities following systemic administration of potent immunomodulators limit dosing and, consequently, efficacy. To address these safety considerations and improve treatment efficacy, interest in local delivery at the site of the tumor has increased. Numerous intratumorally delivered immunotherapeutics have been and are being explored clinically and preclinically, including monoclonal antibodies, cellular therapies, viruses, nucleic acids, cytokines, innate immune agonists, and bacteria. This review summarizes the current and past intratumoral immunotherapy clinical landscape in breast cancer as well as current progress that has been made in preclinical studies, with a focus on delivery parameters and considerations. Figure 1. Intratumoral immunotherapies being explored in clinical and preclinical studies in breast cancer treatment include monoclonal antibodies, cellular therapies, viruses, nucleic acids, cytokines, innate immune agonists, and bacteria 1.